Sustainable budget allocation strategy in supporting SDGs environmental pillar in Malang City, Indonesia - Aini, Asfa Agustina Nusba; Rahmawati, Farida; Sumarsono, Hadi (Publisher of Widyagama University of Malang (UWG Press), 2024)
Sustainable Development Goals (SDGs) consist of three pillars: economic, social and environmental. It has been observed that the environmental pillar in Malang City has declined, while the economic and social pillar have increased, indicating that economic and human activities in general have a big influence on reducing environmental quality. This research focuses on evaluating sustainable budget allocation strategies that support the environmental pillar. Budget efficiency analysis was used to assess SDGs achievement in Malang City from 2019 to 2022. Based on the calculation results of this research, Malang City's budgeting efficiency was in the